Enhanced gypsum scaling by organic fouling layer on nanofiltration membrane: Characteristics and mechanisms. (15th March 2016) - Wang, Jiaxuan; Wang, Lei; Miao, Rui; Lv, Yongtao; Wang, Xudong; Meng, Xiaorong; Yang, Ruosong; Zhang, Xiaoting
Abstract: To investigate how the characteristics of pregenerated organic fouling layers on nanofiltration (NF) membranes influence the subsequent gypsum scaling behavior, filtration experiments with gypsum were carried out with organic-fouled poly(piperazineamide) NF membranes. Organic fouling layer on membrane was induced by bovine serum albumin (BSA), humic acid (HA), and sodium alginate (SA), respectively. The morphology and components of the scalants, the role of Ca 2+ adsorption on the organic fouling layer during gypsum crystallization, and the interaction forces of gypsum on the membrane surface were investigated. The results indicated that SA- and HA-fouled membranes had higher surface crystallization tendency along with more severe flux decline during gypsum scaling than BSA-fouled and virgin membranes because HA and SA macromolecules acted as nuclei for crystallization. Based on the analyses of Ca 2+ adsorption onto organic adlayers and adhesion forces, it was found that the flux decline rate and extent in the gypsum scaling experiment was positively related to the Ca 2+ -binding capacity of the organic matter. Although the dominant gypsum scaling mechanism was affected by coupling physicochemical effects, the controlling factors varied among foulants. Nevertheless, the carboxyl density of organic matter played an important role in determining surface crystallization on organic-fouled membrane. Graphical abstract: Highlights: Poly(piperazineamide)-coated quartz crystal sensor was prepared. The interaction forces of gypsum–membrane and gypsum–gypsum were measured. Gypsum scaling was accelerated by the organic fouling layer. Carboxyl density of the organic fouling layer plays a key role in gypsum scaling.